Climate change will lead to local extinctions and mismatched range contractions disrupting bee-dependent crop pollination - Oliveira, Willams; Cruz-Neto, Oswaldo; Silva, Jéssica L. S.; Tabarelli, Marcelo; Peres, Carlos A.; Lopes, Ariadna V. (Frontiers in Bee Science, 2025)
Climate change is one of the main drivers of biological reorganization, population decline of pollinators, and disruption of species interactions. These impacts represent a major threat to crop pollination and human food security. Here, we tested the hypothesis that the spatial mismatches between Neotropical food plant species and their bee pollinators are exacerbated under scenarios of projected climate change. To investigate this hypothesis we performed species distribution modeling to simulate the effects of climate change on suitable habitats for the occurrence of both native food plants and their main pollinators. We selected three economically important food plants native to Brazil bearing a self-incompatible reproductive system that is strictly dependent on pollinators: (1) Bertholletia excelsa, (2) Eugenia uniflora, and (3) Passiflora edulis; and we selected the main effective bee pollinators of each plant species: (1) Apis mellifera (i.e., pollinator of E. uniflora), (2) Eulaema mocsaryi (i.e., pollinator of B. excelsa), and (3) Xylocopa frontalis (i.e., pollinator of P. edulis). We documented that climate change will likely distinctly affect areas of suitable habitats for food plants and their main bee pollinators across Brazil, in which all species will likely experience contractions in their ecological niches. In addition, we also documented that suitable habitats were reduced for the co-occurrence of all food plants and their pollinators. Specifically, 51.5% for P. edulis and X. frontalis, 76% for B. excelsa and E. mocsaryi, and 54% for E. uniflora and A. mellifera. Therefore, these findings underscore that plausible climate change scenarios can act as a potential driver of spatial mismatches between food plants and their main pollinators, disrupting the pollination of these food plants. Our results show that plant and pollinator species respond negatively to the impacts of climate change under all scenarios, which can result in alarming projections for strictly bee-pollinated self-incompatible plant species. This study reaffirms that bees are sensitive to climate change, highlighting the negative impact even for the exotic European honeybee, Apis mellifera. Finally, climate change could impact crop pollination, with detrimental implications for food production and food security.